Poverty and Violence : The Immediate Impact of Terrorist Attacks against Civilians in Somalia - Nunez-Chaim, Gonzalo; Pape, Utz Johann (World Bank, Washington, DC, 2022)
Somalia, one of the poorest countries in Sub-Saharan Africa, still faces many challenges as it remains fragile. Terrorist groups and their attacks are threatening the government and limiting its capacity to implement effective development policies. Using difference-in-difference and instrumental variables approaches with micro-data from two waves of the Somali High Frequency Survey, this paper estimates the immediate (within a week) impact of terrorist attacks on households. The consumption of households exposed to terrorist incidents decreases by 33 percent, mainly on food items. As a result, poverty and the depth of poverty among the poor increases. The decline in consumption seems to be explained by a smaller share of household members working and earning income after an attack. In addition, the effect on consumption is restricted to a 4-kilometer radius from incidents and has a heterogeneous impact, not affecting households in the top 20 percent of the consumption distribution. The paper also finds a deterioration in people’s perception of police competence. Achieving peace is a fundamental first step to increase welfare conditions that will also bring other wider long-term benefits in Somalia.